1990
DOI: 10.3354/meps061075
|View full text |Cite
|
Sign up to set email alerts
|

Plankton community respiration along a nutrient gradient in a shallow Danish estuary

Abstract: Plankton community respiration was examined in a shallow, very eutrophic Danish estuary during April to September. Maximum rates (3.98 g O2 m-3 d-l) were measured during the phytoplankton spring bloom in the most eutrophicated inner parts. Community respiration was significantly related to biomass and gross productivity of phytoplankton and net production of bacterioplankton. The relationship was weak to temperature and bacterial biomass. Regression analysis suggested that phytoplankton and bacteria, on averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
71
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 16 publications
10
71
1
Order By: Relevance
“…The seasonal rates reported here are in very good agreement with the seasonal average of 2.1 g C m-' d-' derived from intensive I4C-uptake measurements series in the middle segment of the nearby Ria de Arosa during the upwelling season (1989) (Alvarez-Salgado et al 1996a). Comparison with other upwelling systems for which primary production was measured over either complete upwellingrelaxation cycles or entire upwelling season indicated that the rate of primary production in the Ria d e Vigo is comparable to averaged values recently reported for the NE Pacific (2.6 g C m-'d-'; Pilskaln et al 1996), NW African (0.7 to 4.7 g C m-' d-l; Minas et al 1986) and Benguela (Hopkinson 1985, Kuparinen 1987, Jensen et al 1990, Kemp et al 1992, Blight et al 1995. Though short-term variability of respiration rates as high as that observed in the present study has not been previously reported, the vertical and longterm seasonal distribution of DCR in the Ria de Vigo presented an overall pattern similar to that observed in another seasonally stratified coastal system in the Baltic Sea (Kuparinen 1987).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The seasonal rates reported here are in very good agreement with the seasonal average of 2.1 g C m-' d-' derived from intensive I4C-uptake measurements series in the middle segment of the nearby Ria de Arosa during the upwelling season (1989) (Alvarez-Salgado et al 1996a). Comparison with other upwelling systems for which primary production was measured over either complete upwellingrelaxation cycles or entire upwelling season indicated that the rate of primary production in the Ria d e Vigo is comparable to averaged values recently reported for the NE Pacific (2.6 g C m-'d-'; Pilskaln et al 1996), NW African (0.7 to 4.7 g C m-' d-l; Minas et al 1986) and Benguela (Hopkinson 1985, Kuparinen 1987, Jensen et al 1990, Kemp et al 1992, Blight et al 1995. Though short-term variability of respiration rates as high as that observed in the present study has not been previously reported, the vertical and longterm seasonal distribution of DCR in the Ria de Vigo presented an overall pattern similar to that observed in another seasonally stratified coastal system in the Baltic Sea (Kuparinen 1987).…”
Section: Discussionmentioning
confidence: 52%
“…In marine pelagic systems mental biological processes driving the flwes of organic with limited external inputs of organic matter, phytoplankton primary production is the principal source of organic carbon and the balance between the 2 pro-and community respiration is subject to a number of physical and biological interactions which cause the 2 processes to be separated in time and space (Williams 1984, Smith & Kemp 1995. While measurements of primary production have been carried out routinely in the marine environment for several decades (Peterson 1980), it is only comparatively recently that sufficiently precise and automated methods for oxygen determination have made intensive measurements of respiration rates possible (Kuparinen 1987, Kenney et al 1988, Jensen et al 1990, Griffith et al 1990, Kemp et al 1992, Blight et al 1995. For this reason, the factors controlling the seasonal and short-term balance between primary production and respiration processes in marine pelagic systems are still poorly understood (Sherr & Sherr 1996, del Giorgio et al 1997, Geider 1997).…”
Section: Introductionmentioning
confidence: 99%
“…3a), although variations in P T explained only 48% of the seasonal and spatial variability in R T . Significant positive relationships between P T and R T appear to be common features of aquatic systems, both within individual systems (e.g., Jensen et al 1990) and across a range of systems (e.g., Duarte and Agustí 1998;Williams 1998). A relationship between P T and R T is commonly taken as evidence of the importance of autochthonous production in supplying the organic matter to sustain heterotrophic activity within the ecosystem (Hopkinson 1985;Blight et al 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Perspectives on metabolic balance may also be influenced by whether P versus R relations are modeled as linear or power functions (cf., Duarte and Agustí 1998;Williams and Bowers 1999). As is the convention for analyzing plankton metabolism data from a single coastal environment (e.g., Hopkinson 1985;Jensen et al 1990;Iriarte et al 1996), we used a linear model for our analysis of P versus R relationships. As both P and R include associated measurement error, however, linear regressions were performed using model II regression techniques following the equations of Ricker (1973).…”
Section: Resultsmentioning
confidence: 99%
“…Cole et al (1991) deduced that phytoplankton respiration could not amount to much more than 5% of lightsaturated hourly primary production per unit Chl a (P ) if b max NPP were to be, in fact, positive within the tidal freshwater Hudson River. Similarly, Jensen et al (1990) concluded from regression analysis that hourly phytoplankton respiration amounted to ϳ6% of gross primary production in a shallow, eutrophic Danish estuary. Although the true magnitude and variability of phytoplankton respiration and the influence of photoadaptation are unknown, we conclude that our estimates of diurnal NPP are probably higher than in situ rates.…”
Section: Discussionmentioning
confidence: 99%